2009
DOI: 10.2353/ajpath.2009.090018
|View full text |Cite
|
Sign up to set email alerts
|

Cell Death and Learning Impairment in Mice Caused by in Vitro Modified Pro-NGF Can Be Related to Its Increased Oxidative Modifications in Alzheimer Disease

Abstract: Pro-nerve growth factor (pro-NGF) is expressed at increased levels in Alzheimer's disease (AD)-affected brains and is able to induce cell death in cultures; however, the reasons for these phenomena remain elusive. Here we show that pro-NGF in human ADaffected hippocampus and entorhinal cortex is modified by advanced glycation and lipoxidation end-products in a stage-dependent manner. These modifications block pro-NGF processing to mature NGF, thus making the proneurotrophin especially effective in inducing apo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
37
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(42 citation statements)
references
References 36 publications
(52 reference statements)
5
37
0
Order By: Relevance
“…A recent report suggested that pro-NGF observed in AD brains has undergone oxidative modifications by advanced glycation and lipid peroxidation that inhibit the processing of pro-NGF to its mature form, thereby resulting in an imbalance between the precursor and mature forms of the protein (Kichev et al, 2009). This altered processing favors the pro-apoptotic cascade mediated by enhanced levels of pro-NGF and is also consistent with the reduced levels of NGF and cholinergic degeneration observed in models of AD (Cuello and Bruno, 2007; Cuello et al, 2007; Cuello and Canneva, 2008; Cuello et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…A recent report suggested that pro-NGF observed in AD brains has undergone oxidative modifications by advanced glycation and lipid peroxidation that inhibit the processing of pro-NGF to its mature form, thereby resulting in an imbalance between the precursor and mature forms of the protein (Kichev et al, 2009). This altered processing favors the pro-apoptotic cascade mediated by enhanced levels of pro-NGF and is also consistent with the reduced levels of NGF and cholinergic degeneration observed in models of AD (Cuello and Bruno, 2007; Cuello et al, 2007; Cuello and Canneva, 2008; Cuello et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Some unexpected findings with respect to neurotrophin signaling in the nervous system are the ability of NGF and BDNF to induce apoptosis via p75NTR when Trk signaling is absent versus mediating survival when Trk signaling is present (Casaccia-Bonnefil et al, 1996;Friedman, 2000); and the ability of proNGF and proBDNF to bind p75NTR and form a high-affinity complex with the receptor sortilin that interacts with the prodomains of the proneurotrophins, thereby initiating apoptotic signaling cascades Jansen et al, 2007). In the latter, activation of the polyol pathway, a feature of the diabetic neuropathic state driven by excess glucose (Calcutt et al, 2009), leads to advanced glycation/lipoxidation end products inducing oxidative modifications that render the pro-NGF resistant to processing, thereby increasing its effectiveness as a pathologic ligand through its ability to induce apoptosis (Kichev et al, 2009). In the latter, activation of the polyol pathway, a feature of the diabetic neuropathic state driven by excess glucose (Calcutt et al, 2009), leads to advanced glycation/lipoxidation end products inducing oxidative modifications that render the pro-NGF resistant to processing, thereby increasing its effectiveness as a pathologic ligand through its ability to induce apoptosis (Kichev et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…At variance with the acute intracerebroventricular proNGF injections in rodents, 38,39 chronic exposure to high proNGF levels determines signs of AD neurodegeneration in transgenic mice. Although no abnormal tau pathology was found, a significant positivity for Ab and oligomeric Ab species was detected.…”
mentioning
confidence: 99%